Academic Advising in Civil Engineering: Design and Evaluation of a Hybrid Model - Jennifer Keenahan; Miguel Casero; Sarah Cotterill; Fiachra O’Loughlin; John O’Sullivan; Shane Donohue; Daniel McCrum; Arturo Gonzalez; Páraic Carroll; Patrick Purcell (Education Sciences, 2022)
A project to formalise and expand Academic Advising has been implemented at the UCD Civil Engineering School. The goals of this project were twofold: on the one hand, it aimed at training faculty members in Academic Advising roles and providing them with the necessary resources. On the other hand, the project sought to expand student interaction, in particular by engaging students informally in order to build a rapport between them and the academic advisors that we expect will bring long term benefits. The resulting model combines elements of both the prescriptive, e.g., formal training, informative talks on key topics, and developmental approaches, e.g., coffee mornings for students and faculty members. The evaluation of the project was carried out through questionnaires and focus groups. It highlighted very positive feedback from the students, who find these new lines of communication with the academic staff to be useful and productive.